2023
DOI: 10.2174/1573399819666221031161442
|View full text |Cite
|
Sign up to set email alerts
|

Using Real-Time, Partially Automated Interactive System to Interpret Patient’s Data; Helping The Patient To Achieve Diabetic Self-Management: A Rapid Literature Review

Abstract: Background: Diabetes is an endocrine chronic condition with a high prevalence rate among the population that needs a complex management process. However, many advanced health care technologies were evolving to help patients to achieve their centered care and self-management using real-time proactive techniques through interactive systems to detect early complications and prevent them. the purpose of the current review is to assess the findings of literature reviews of the main interventions that used a real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Natural Language Processing (NLP), a branch of AI, is crucial in handling the unstructured data included in electronic health records [ 13 ]. Symptoms, diagnoses, and treatment outcomes are just a few examples of the essential information that medical notes in the EHR frequently contain in an unstructured format.…”
Section: Revolutionizing Cancer Clinical Trials: the Integral Role Of...mentioning
confidence: 99%
“…Natural Language Processing (NLP), a branch of AI, is crucial in handling the unstructured data included in electronic health records [ 13 ]. Symptoms, diagnoses, and treatment outcomes are just a few examples of the essential information that medical notes in the EHR frequently contain in an unstructured format.…”
Section: Revolutionizing Cancer Clinical Trials: the Integral Role Of...mentioning
confidence: 99%
“…Also, lack of HL is recognized as a stronger predictor of poor health than age, income, employment, educational level, or race [7]. It has been found that people with inadequate HL have difficulty understanding labels and prescriptions, participating in medical decisions, following medical recommendations, and attending their follow-up appointments [8]. Individuals with inadequate or marginal HL have major challenges with poor self-care behaviors and receive fewer preventive measures, leading to increase causes of mortality [9].…”
Section: Introductionmentioning
confidence: 99%